2017
DOI: 10.1002/tal.1398
|View full text |Cite
|
Sign up to set email alerts
|

Case study of the seismic response of an extra‐dosed cable‐stayed bridge with cable‐sliding friction aseismic bearing using shake table tests

Abstract: This paper presents an experimental case study of an extra-dosed cable-stayed bridge isolated by cable-sliding friction aseismic bearing (CSFAB) based on 1/20 scaled half structure multiple shake

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The half-structure model inevitably neglects the contributions of symmetric vibration modes of the deck. As discussed earlier, a limited number of previous researches (Wang et al, 2016; Xu, 2015; Yang et al, 2017) have shown that such simplification is generally adequate for the structural responses (girder-end displacements, tower-base moment, etc.) under longitudinal uniform excitations.…”
Section: Proposed Half-bridge Simplified Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-structure model inevitably neglects the contributions of symmetric vibration modes of the deck. As discussed earlier, a limited number of previous researches (Wang et al, 2016; Xu, 2015; Yang et al, 2017) have shown that such simplification is generally adequate for the structural responses (girder-end displacements, tower-base moment, etc.) under longitudinal uniform excitations.…”
Section: Proposed Half-bridge Simplified Methodsmentioning
confidence: 99%
“…FEAs showed that the dynamic responses of the full-bridge and the half-bridge model under uniform excitations are sufficiently close for engineering purposes. Based on the numerical studies of Wang et al (2016), Yang et al (2017) conducted shaking table tests of a cable-stayed bridge with cable-sliding friction aseismic bearing (CSFAB) under uniform seismic excitations. The shaking table tests used a 1:20 scale model of the half structure with a horizontal roller at the axis of symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…basin-type rubber bearing and panel-type rubber bearing. In general, the rubber bearing has very large compressive stiffness and load-carrying capacity in vertical direction, and provides frictional restoring force in horizontal directions (Yang et al 2017;Jiang et al 2019;Ding et al 2019). In practical design, the rubber bearing was simplified as a linear spring both in vertical compression and tension.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, shake table tests for bridge structures were gradually carried out, including tests for the crucial bridge members (i.e. piers [42][43][44], bearings [45], foundations [46]) as well as entire bridge structures [47][48][49][50][51][52]. Notwithstanding the progress made, the above tests study straight bridges with only few of them focusing on curved ones.…”
Section: Introductionmentioning
confidence: 99%